Toxicity of Azadirachta indica to leaf-cutting ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Santos-Oliveira, M. F S [UNESP]; Bueno, O. C. [UNESP]; Marini, T. [UNESP]; Reiss, I. C. [UNESP]; Bueno, F. C. [UNESP] (My University, 2006)
The leaf-cutting ants are responsible for great economical damages in cultivated areas, and because of this characteristic, they have aroused the interest of researchers around the world. Thus, extracts of neem (Azadirachta indica, A. Juss) were tested through ingestion and contact experiments to investigate their toxicity to Atta sexdens rubropilosa workers. Crude extract of neem seed oil was toxic to the ants by ingestion in all concentrations tested but no toxicity was observed in contact experiments. However, crude extract of neem seed paste produced a significant toxicity to workers by ingestion and by contact.
Keywords: Control; Leaf-cutting ant; Natural products; Neem; Vegetable oil; Atta; Atta sexdens rubropilosa; Azadirachta indica; Formicidae; Hymenoptera